A portrait of the ecological clusters in the urban fringe area of Surakarta, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Sari CP, Santosa SHMB, Marsono D. 2021. A portrait of the ecological clusters in the urban fringe area of Surakarta, Indonesia. Biodiversitas 23: 670-679. The population growth in Surakarta has led to agglomeration. To fulfill human needs, Surakarta has seen some major land-use changes across decades. The availability of natural resources and ecosystem services is very important for the sustainability of life. Biodiversity index-based area management is one of the best ways. Cluster methods will facilitate the planning, implementation and subsequent management of an area. This study divides the urban fringe of Surakarta into 48 ecological units. The biotic analysis of biodiversity index calculations is used to assess all ecological units. The value of the biodiversity indices is the basis for forming clusters. From the statistical analysis, 5 clusters were formed based on the level of similarity. The majority of the clusters were located in Karanganyar District. Cluster 3 was the cluster with the most members and the most value of the index of biodiversity. Cluster 2 had only 2 clusters. The range of biodiversity index in each cluster was not much different. The richness of the species in each cluster was in the medium-high range (tree level 0.945-4.500, saplings 0.908-4.889 and seedlings 0.638-4.440). The diversity of the species was at a moderate level with the tree level diversity index value of 2.044-2.290, saplings 1.610-2.294, seedlings 1.557-2.291 and was at a moderate level with the tree level index evenness value of 0.735-1.421, saplings 0.641-1.412, seedlings 0.730-1.645. In each cluster, the condition of the biodiversity was quite good and able to support the function and services of the ecosystem of urban areas and urban fringes. There was no dominance of plants, and the types were still diverse for the ecosystem stability. The development of Surakarta was faster in the south and the north. Biodiversity in eastern Surakarta was found to be more effective in supporting the ecosystem services of Surakarta City.